Pertimbangan Fluktuasi Populasi Dalam Perhitungan Efikasi Pestisida = Considering Population Fluctuation In Calculating Pesticides' Efficacy - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Teknik UGM, 1999)
Efficacy trials are carried out to secure registration and distribution permit for pesticides in a given country. In Indonesia, the protocol exclusively relies on the statistical difference between treatments and check plots, with little regard to before-treatment population. The efficacy criterion and its defined formulas with more attention to population changes are available, and should be applied to increase the efficacy's accuracy.